ANALISIS SISTEM ANTREAN PELAYANAN DI KANTOR PERTANAHAN KOTA SEMARANG - Lenti Agustina Lianasari Tambunan; Sugito Sugito; Hasbi Yasin (Jurnal Gaussian, 2014)
Kantor Pertanahan Kota Semarang in charge of the land with an area of 373.70 km2 coverage, every day crowded with visitors who want to take care of the land petition. However, the high number of applicants who must be served not proportional to the number of care facilities available to the applicant should enter the waiting list queue or experiencing situation. This situation occurs in almost all counters, namely Counter 1 Land Information, Counter 2 Registration, Counter 3 Payment, and Counter 4 Product Delivery. Therefore, the required analysis is based on the model line system in accordance with the conditions of service which can then be used to address the issue queue. Based on the analysis, the model system is the best line in counter 1 land information (M/M/1): (GD/∞/∞). Counter 2 registration which is divided into 7 sub-counters have a model (M/M/2): (GD/∞/∞) to sub counters 2A, 2B, 2C, 2E/F, 2G, 2H, and the model (M/M/4): (GD/∞/∞) to sub counter 2D. Counter 3 payment (M/M/2): (GD/∞/∞). Counter 4 is the product delivery (M/M/2): (GD/∞/∞).Keywords :  Queuing system, Service, Arrivals